(untitled) (Journal of International Studies, 2020)
This article makes a critical analysis of Zimbabwe’s contribution to peacekeeping and peace-support operations in the period 1980 to 2000. It argues that this contribution has brought in a new thrust of peacekeeping operations of coercing the other party to the negotiating table. The article demonstrates the complexity of traditional peacekeeping operations where member states (and in this case Zimbabwe) have made notable contribution to the cause of peacekeeping operations, not only through traditional methods and principles of peacekeeping but also through various other methodologies such as peace-support efforts. Using the 1980 to 2000 time frame, in case studying Zimbabwe’s contribution to peace support operations, this article demonstrates that even developing countries have the capacity and political willingness to shape international activities.